Factors influencing employee performance / Fatin Nasuha Abdullah - Abdullah, Fatin Nasuha (Faculty of Business and Management, 2018)
This study examines the factors of compensation, work-life conflict, leadership and working conditions that influence employee performance. Questionnaire has been used as a research instruments were used to obtain data. A total of 97questionnaires were distributed for the respondents at Urban Transformation Centre (UTC) Melaka. The sample of study and data was then being analysed using the Statistical Package for Social Science. The tests involved are Descriptive Analysis, Reliability Analysis, Pearson Correlation and Multiple Regression Analysis. The multiple regression analysis result showed that there is significant relationship between leadership and working condition, and employee performance.